PSYCHOTIC DISORDERS IN PEOPLE USING SYNTHETIC CANNABINOIDS (SPICE) - L. A. Ivanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The study involved the group of patients (n = 40) with psychotic disorders who used synthetic cannabinoids (spice). Among the psychotic disorders according to ICD-10 we allocated intoxication delirium (F12.03; 35 %), schizophreniform disorder (F12.50; 60 %), disorder with predominantly manic psychotic symptoms (F12.55; 5 %). The average age of patients was 25.2 ± 4.4 years. Hereditary aggravation in patients who consume synthetic cannabinoids was presented by alcoholism and substance abuse (20 %), affective disorders (7.5 %), schizophrenia (5 %); personality disorders (10 %); suicides (2.5 %). The group of patients with intoxication with delirium had significantly higher frequency of family history of alcoholism and addiction to psychoactive substances compared with patients with schizophreniform disorder (p < 0.02). Clinic intoxication delirium was characterized by disturbance of consciousness (delirium, twilight) lasting from several hours to 2-3 days, psychomotor agitation, aggression, shouting certain phrases and words, anxiety, fear, visual hallucinations. In patients with acute schizophreniform disorder (24 patients; 60 %) symptoms consisted of a dominant affect (depressive, or mixed), productive psychopathological symptoms within the list of F20 headings of ICD-10. Productive syndromes were limited to verbal hallucinosis (true or its limiting variants) in the form of voiced (which discuss the patient's behavior, threaten him/her with death, offer advice), reference of persecutory delusion. The coming out of a psychotic state was characterized by short-term postpsychotic depression. Patients received detoxification therapy and also combined psychopharmacotherapy with the use of antipsychotics, antidepressants, tranquilizers, normotymics, nootropics.